Analysis of Contractility and Invasion Potential of Two Canine Mammary Tumor Cell Lines - Rajakylä, Kaisa; Krishnan, Ramaswamy; Tojkander, Sari (Frontiers in Veterinary Science, 2017)
Cancer cells are surrounded by a mechanically and biochemically distinct microenvironment that undergoes dynamic changes throughout the neoplastic progression. During this progression, some cancer cells acquire abnormal characteristics that potentiate their escape from the primary tumor site, to establish secondary tumors in distant organs. Recent studies with several human cancer cell lines have shown that the altered physical properties of tumor cells, such as their ability to apply high traction forces to the surroundings, are directly linked with their potential to invade and metastasize. To test the hypothetical interconnection between actomyosin-mediated traction forces and invasion potential within 3D-microenvironment, we utilized two canine mammary tumor cell lines with different contractile properties. These cell lines, CMT-U27 and CMT-U309, were found to have distinct expression patterns of lineage-specific markers and organization of actin-based structures. In particular, CMT-U309 carcinoma cells were typified by thick contractile actomyosin bundles that exerted high forces to their environment, as measured by traction force microscopy. These high contractile forces also correlated with the prominent invasiveness of the CMT-U309 cell line. Furthermore, we found high contractility and 3D-invasion potential to be dependent on the activity of 5´AMP-activated protein kinase (AMPK), as blocking AMPK signaling was found to reverse both of these features. Taken together, our findings implicate that actomyosin forces correlate with the invasion potential of the studied cell lines.